The mechanical strength analysis on the pool tub of loop heat pipe prototype using CATIA software - Dedy Haryanto; Giarno Giarno; G. Bambang Heru K; Ainur Rosidi; Nursinta Adi Wahanani; Mukhsinun Hadi Kusuma (Jurnal POLIMESIN, 2022)
The NuScale Small Modular Reactor operates using a fully passive cooling system. Under normal operating conditions, the cooling water used to immerse the reactor has a temperature range of 30°C – 40°C. To reduce additional water due to evaporation, the use of a loop heat pipe (LHP) as a heat sink in the pool cooling water can reduce evaporation and increase the economic value of NuScale operations. To get a further basic understanding of LHP as an additional passive cooling system, a small-scale LHP prototype was made at the Center for Nuclear Reactor Technology and Safety, National Nuclear Energy Agency. This LHP prototype consists of several components, including a pool tub unit that simulates a pool of cooling water immersing the reactor. This research focuses on analyzing the mechanical strength of the pool tub before it is made and used as an experimental tool. The purpose of the analysis is to determine the mechanical strength of the pool tub including mechanical stress and translational displacement related to the level of safety and design safety. The method used is to simulate using CATIA software to analyze the mechanical strength of a swimming pool by making a 3-dimensional model according to an existing design, providing restraint on a 3-dimensional model, providing loads in the form of pressure and temperature on a 3-dimensional model, and testing mechanical strength. The simulation results show that the mechanical stress produced is 1.96 x 108 N/m2 at the bottom of the pool tub. The mechanical stress that occurs is smaller than the yield strength of the AISI 1040 Carbon Steel material, which is 3.5 x 108 N/m2. The translational displacement obtained of 0.844 mm is very small when compared to the dimensions of the pool basin, so it does not result in changes in the shape of the pool basin when pressure and temperature are given during the experiment. The conclusion of this simulation shows that the design of the pool tub unit is safe to manufacture and operate during the experiment.